2012
DOI: 10.12816/0003610
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Banking : The Controversy Over Non-Interest Banking System in Nigeria

Abstract: The Central Bank of Nigeria (CBN) approval of a Non-interest Islamic banking in Nigeria has generated a lot of controversy along religious divide and this motivated the study. It was descriptive study that relied on secondary sources of data and adopted content analysis method. It observed that Nigeria is a secular State and issues bordering on religion are sensitive and explained why the opposition to it assumed religious dimension. The study found that the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…These results indicate that digital technologies aid mass communication in different ways in this era of digital communication. It agrees with the expression by Alao [2], which avers that the mass media have a way of incorporating new forms of technology into common mass communication activities. New forums and opportunities have been opened by various technologies for the field of mass communication, and they are constantly developing.…”
Section: Discussion Of Findingssupporting
confidence: 88%
See 1 more Smart Citation
“…These results indicate that digital technologies aid mass communication in different ways in this era of digital communication. It agrees with the expression by Alao [2], which avers that the mass media have a way of incorporating new forms of technology into common mass communication activities. New forums and opportunities have been opened by various technologies for the field of mass communication, and they are constantly developing.…”
Section: Discussion Of Findingssupporting
confidence: 88%
“…This is because the mass media have a way of incorporating new forms of technology into common mass communication activities. New forums and opportunities have been opened by various technologies for the field of mass communication, and they are constantly developing [2].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this usually leads to a heated debate on the desirability of the Islamic banking. Many scholars found that Islamic banking is rejected by many non-Muslims based on emotional reasons but not for the economic stands (Alao and Alao, 2012;Nkwatoh and Mallum, 2014). Similarly, Ajani et al (2013) argued that it is difficult for individuals or corporate bodies to float full-fledged Islamic banks or financial institutions in Nigerian environment.…”
Section: Introductionmentioning
confidence: 99%
“…Efe, 2013; Ameh et al. , 2016; Alao, 2013; Ademiluyi and Aluko-Arowolo, 2009). A referral system is intended to extend access to urban centres for those living in rural areas; however, this system does not function effectively (Abdulraheem et al.…”
Section: Research Questions For Rural Healthcare Workers (Rhcws)mentioning
confidence: 99%